2021
DOI: 10.1111/tmi.13642
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of integrated studies on antimicrobial resistance genes in Africa—A One Health perspective

Abstract: Background: Increasing antimicrobial resistance (AMR) raises serious health and financial concerns. However, the main drivers of the emergence, spread and subsequent colonisation of resistant bacterial strains between humans, animals and the environment are still poorly understood.Objective: The aim of this review was to identify molecular studies on AMR in One Health settings in Africa and to determine the prevalence of antimicrobial resistance genes in humans, animals and the environment. Due to the very low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 28 publications
(38 reference statements)
2
18
0
Order By: Relevance
“… 49 The number of interdisciplinary studies included in this review was low (7%; n=9/130; Figure 3 ). Similarly, O’Neal et al review for Central America 50 and Escher et al review for Africa 51 found small numbers of One Health-related studies. Thus, apart from South America, other world regions also struggle to incorporate One Health approaches to their experimental designs; a reality that might be tackled with international cooperation, executing multi-sectorial action plans as proposed by the WHO.…”
Section: Discussionmentioning
confidence: 96%
“… 49 The number of interdisciplinary studies included in this review was low (7%; n=9/130; Figure 3 ). Similarly, O’Neal et al review for Central America 50 and Escher et al review for Africa 51 found small numbers of One Health-related studies. Thus, apart from South America, other world regions also struggle to incorporate One Health approaches to their experimental designs; a reality that might be tackled with international cooperation, executing multi-sectorial action plans as proposed by the WHO.…”
Section: Discussionmentioning
confidence: 96%
“…Only records that were available on or after January 1, 2000 were included based on related systematic reviews using this cutoff. 18 , 32 Likewise, “resistome” was not used in scientific literature before 2006, 33 so, to reduce the number of studies only assessing a subset of ARGs in the resistome but not exclude resistome-type studies published before 2006, the cutoff of 2000 was used as a conservative restriction. Only papers written in English were included due to resource limitations.…”
Section: Methodsmentioning
confidence: 99%
“… 12 Perturbations to the gut microbiome have been associated with numerous health concerns including loss of colonization resistance, 8 , 13 an increase in potentially pathogenic antibiotic-resistant organisms, 14 and reduced microbiome resiliency due to decreases in strain-level diversity. 15 , 16 Systematic literature reviews have attempted to assess the human gut resistome, 17 , 18 but persistent gaps remain, including our understanding of how perturbations lead to alterations in ARG composition and diversity.…”
Section: Introductionmentioning
confidence: 99%
“… 8 For instance, antimicrobial‐resistant bacterial strains could lead to untreatable infections and cause 10 million deaths each year by 2050. 9 Understanding AMR in Africa post‐COVID‐19 can prevent its extension and avoidable deaths. However, little is known about AMR in the post‐COVID‐19 context in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…It is a public health problem that transcends continents and national borders and is rapidly growing, as seen with the sixfold increase in resistance rates since 2017 8 . For instance, antimicrobial‐resistant bacterial strains could lead to untreatable infections and cause 10 million deaths each year by 2050 9 . Understanding AMR in Africa post‐COVID‐19 can prevent its extension and avoidable deaths.…”
Section: Introductionmentioning
confidence: 99%